2017
DOI: 10.1097/mbc.0000000000000616
|View full text |Cite
|
Sign up to set email alerts
|

Relation of coagulation factor XI with incident coronary heart disease and stroke

Abstract: OBJECTIVES The role of coagulation factor XI (FXI) in the etiology of arterial thrombotic events remains uncertain. We examined the association of FXI with incident coronary heart disease (CHD), ischemic stroke (IS), and hemorrhagic stroke (HS). METHODS Data were from 3394 adults (mean age: 74.5 years) enrolled in the Cardiovascular Health Study who had FXI antigen from plasma samples drawn in 1992–1993 and were followed for cardiovascular events until June 30, 2013. RESULTS Approximately 63% of participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Inactivating mutations of F11 are relatively common among Ashkenazi Jews (33). A number of studies investigated the relationship between FXI and incident coronary heart disease, stroke, and ischemic cardiomyopathy (34,35). FXI was reported to improve or protect against the inflammatory responses and cytokine responses to infections independently of its intrinsic coagulation activity (36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivating mutations of F11 are relatively common among Ashkenazi Jews (33). A number of studies investigated the relationship between FXI and incident coronary heart disease, stroke, and ischemic cardiomyopathy (34,35). FXI was reported to improve or protect against the inflammatory responses and cytokine responses to infections independently of its intrinsic coagulation activity (36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Other prospective studies were inconsistent with ours, showing that FXI was not associated with stroke or ischemic stroke in Whites and African Americans. 11 , 15 , 33 However, these prospective studies were all focused on Europeans and Americans, to our knowledge, we first performed the prospective study and found high FXI levels were associated with higher risk of incident stroke and ischemic stroke among Chinese. Thus, the population difference might be a possible explanation for the inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“… 4 A number of studies revealed the relationship between FXI and stroke, coronary heart disease, and ischemic cardiomyopathy. 5 In addition, the observation that mice with FXI overexpression exhibit other systemic metabolic benefits, including less body fat gain and improved lipid homeostasis, suggests potential effects of FXI beyond the heart. Whether other organs respond to FXI and whether these additional effects are mediated by the BMP7‐SMAD1/5 pathway need further investigation.…”
mentioning
confidence: 99%
“…FXI has been found to protect against sepsis in part by enhancing the phagocytic capacity of neutrophils, a mechanism that is independent of activation via FXIIa 4 . A number of studies revealed the relationship between FXI and stroke, coronary heart disease, and ischemic cardiomyopathy 5 . In addition, the observation that mice with FXI overexpression exhibit other systemic metabolic benefits, including less body fat gain and improved lipid homeostasis, suggests potential effects of FXI beyond the heart.…”
mentioning
confidence: 99%
See 1 more Smart Citation